Cruel But Not Unusual : Violence in Families in Canada, 3rd Edition - Vine, Cathy, 1958-; Alaggia, Ramona, 1957- (Book collections on Project MUSE., 2022)
"Violence in families and intimate relationships affects a significant proportion of the population-from very young children to the elderly-with far-reaching and often devastating consequences. Cruel but Not Unusual draws on the expertise of scholars and practitioners to present readers with the latest research and thinking about the history, conditions, and impact of violence in these contexts. For this new edition, chapters have been updated to reflect changes in data and legislation. New chapters include an examination of trauma from a neurobiological perspective; a critical analysis of the "gender symmetry debate," a debate that questions the gendered nature of intimate violence; and an essay on the history and evolution of the women's movement dedicated to addressing violence against women, which advances theoretical developments that remind readers of the breadth of inclusivity that should be at the heart of working in this field."--